Pengaruh Belanja Modal Terhadap Pengangguran di Indonesia - Fahira, Cut Elsa; Chalisa, Devia; Karila, Nurul; Rezaldi, Muammar; Ramadhani, Rezky Wulan; Amri, Khairul (Journal of Law and Economics, 2023)
This research aims to analyze the influence of capital expenditure on the unemployment rate in Indonesia. Using panel data from 30 provinces during the 2007-2015 period. To sharpen the analysis, we divided the provinces into three groups, namely the western region, the central region, and the eastern region. The analysis model used is panel regression with a fixed effect approach. Using 95% confidence, our research provides empirical evidence that capital expenditure can significantly reduce the unemployment rate in Indonesia's western and central regions, whereas for the eastern region, this expenditure does not significantly reduce unemployment